Bad luck - Bosch, Pseudonymous (London Usborne Publishing, 2016)
Reader, beware! This is a BAD book. A VERY BAD book that will bring you nothing but BAD LUCK. Luckily no one would want to read it as it is extremely BORING and contains NO ADVENTURE whatsoever. No magic. No betrayal. and NO DRAGONS. ABSOLUTELY NO DRAGONS.
Keywords: Children Mystery Book; Work of Fiction-Adventure Book